Taste and Historical Awareness in the Music Collection of Leonardo Grimani (c.1778–1832) - Emina Smailbegović (Muzyka)
This paper intends to reflect on the phenomenon of music collecting starting with the collection of Leonardo Grimani, today kept at the Institute of Musicology at the University of Vienna, assembled at the turn of the century and partly related to the repertoire of the Istituto Filarmonico Veneto (1810–22) of which this collector was the founder and patron. The characteristics of this collection – to which external sources such as period newspapers are added – prompt reflections on the different roles played by the Grimani as a collector, without however neglecting the investigation of the fortune and historicization of certain authors and specific opera pieces.